AKTIVIS GENERASI Z: AN WE HANDLE THE PROBLEM?? - Samitha, Sang Made Dwi Okayana; Pradhana, I Putu Dharmawan; Dewi, Diah Fitrya Utami; Vaasa, Regina Samara; Verlioni, Ni Kadek Ayu; Putri, Putu Erlina Ayu Tiara (JURNAL DARMA AGUNG, 2024)
Student activists have various challenges in managing an organization. They are required not only to be able to lead and organize their organizations, they are also expected to remain active and have achievements in the academic field. This study analyzes student activists who are members of student associations receiving the KIP-Kuliah program at Undiknas University in dealing with various organizational and personal problems. This study uses a qualitative approach with technical triangulation in the form of interviews, observation and documentation. The results of this study reveal that students who fall into the Z generation category have various challenges and try to solve various problems they face by prioritizing communication, describing each problem and trying to understand each other. Conflicts that arise are minimized by dialogue and efforts to accommodate various interests. Time management is also an effective solution in minimizing problems related to their duties and functions as activists and student.